THE EFFECT OF APPLYING THINK TALK WRITE STRATEGY ON STUDENTS’ ACHIEVEMENT IN WRITING SPOOF TEXT - Ingrid Laurensia Simanungkalit; Sortha Silitonga (Universitas Negeri Medan, 2014)
This study dealt with the effect of applying Think Talk Write strategy on students’ achievement in writing spoof text. It was an experimental research. The subject was social students of Grade XI, SMA Negeri 17 Medan, which consisted of 113 students. The research was divided into two groups: experimental and control groups. The instrument to collect the data was writing test. The result of the reliability was 0.70, and the test was reliable. The data were analyzed by using t-test formula. The analysis showed the scores of the students in the experimental group were higher than in the control group at the level of significant=0.05 with the degree of freedom (df) 72,t-observed 4.871> t-table 1.994. The findings indicate that applying Think Talk Write strategy significantly affected the students’ achievement in writing spoof text. English teachers are suggested using Think Talk Write strategy in order to improve students’ achievement in writing.